2022
DOI: 10.1093/jjfinec/nbac027
|View full text |Cite
|
Sign up to set email alerts
|

Ask BERT: How Regulatory Disclosure of Transition and Physical Climate Risks Affects the CDS Term Structure

Abstract: We use BERT, an AI-based algorithm for language understanding, to quantify regulatory climate risk disclosures and analyze their impact on the term structure in the credit default swap (CDS) market. Risk disclosures can either increase or decrease CDS spreads, depending on whether the disclosure reveals new risks or reduces uncertainty. Training BERT to differentiate between transition and physical climate risks, we find that disclosing transition risks increases CDS spreads after the Paris Climate Agreement o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 73 publications
2
47
0
Order By: Relevance
“…Consistently, Carbone et al (2021) find that high carbon emissions are associated with higher credit risk, while emissions disclosure and a forward-looking emissions abatement target are associated with lower credit risk. Kolbel et al (2021) document that firms' exposure to transition risk of climate change increases their credit default swap spreads, which reflect a default risk premium. Furthermore, Islam and Singh (2021) show that large banks pay attention to abnormal regional temperatures and cut their lending to small farms, which exacerbates the negative impact of natural disasters on small-farm borrowers' default risk.…”
Section: The Cost Of Equitymentioning
confidence: 99%
“…Consistently, Carbone et al (2021) find that high carbon emissions are associated with higher credit risk, while emissions disclosure and a forward-looking emissions abatement target are associated with lower credit risk. Kolbel et al (2021) document that firms' exposure to transition risk of climate change increases their credit default swap spreads, which reflect a default risk premium. Furthermore, Islam and Singh (2021) show that large banks pay attention to abnormal regional temperatures and cut their lending to small farms, which exacerbates the negative impact of natural disasters on small-farm borrowers' default risk.…”
Section: The Cost Of Equitymentioning
confidence: 99%
“…KPMG's surveys of sustainability reporting provide summaries of the trend in sustainability reporting, integrated reporting and more recently climate‐related reporting. The 2020 survey (KPMG 2020) identified that 80% of N100 companies worldwide (the top 100 companies by revenue in 52 countries and jurisdictions) now report on sustainability, up by 5% since the last survey in 2017, while the reporting rate has reached 90% or more for the G250 group (the world's largest 250 companies by revenue) since 2011. Australia is one of the global leaders in sustainability reporting with a 92% rate among the N100 companies, up from 77% in the 2017 survey.…”
Section: Sustainability Disclosuresmentioning
confidence: 99%
“…4 Varini et al (2020) find that for topic classification of climate change, even a simple BERT model significantly outperforms keyword-based approaches, which tend to generate false positives, leading to low precision, particularly for the analysis of 10-K regulatory reports. Moreover, Kölbel et al (2021) use a BERT model to show that they are superior to other keyword-based approaches like Sautner et al (2020) to identify climate-relevant information that impacts CDS spreads. 5 We extend our model to a climate-related language model in Webersinke et al (2021).…”
Section: The Tcfd Recommendationsmentioning
confidence: 99%